Salivary flow rate, pH and buffering capacity in patients undergoing fixed orthodontic treatment - A prospective study - Anu, V; Madan Kumar, P; Shivakumar, M (Indian journal of dental research, 2019)
Background: Human saliva has got many important functions like lubrication of the oral tissues, making oral functions like speech, mastication and deglutition possible and also protecting teeth and oral mucosal surfaces in different ways. Dental Caries is one of the common complications in patients undergoing orthodontic treatment. Subjects with impaired saliva flow rate often show high caries incidence. A low flow rate combined with a low or moderate buffer effect clearly indicates poor salivary resistance against microbial attack. Aim: To investigate the changes in stimulated and unstimulated salivary flow rate, pH and buffer capacity in patients undergoing therapy with fixed orthodontic appliances. Materials and Methods: Salivary flow rate, pH and buffering capacity of 20 patients who underwent fixed orthodontic treatment at Department of Orthodontics, Ragas Dental College and Hospital, Chennai were examined using GC saliva check buffer kit. The procedure was carried out during the initiation of orthodontic treatment and subsequently, one month and six months after the placement of appliance. Results: Results showed there was a significant increase in the salivary flow rate one month and six months after placement of fixed appliance while pH and buffering capacity showed no significant changes. Conclusion: Salivary flow rate increases significantly during fixed orthodontic treatment. Salivary pH and buffering capacity showed no significant changes suggesting that they are not sole factors for demineralization in orthodontic patients.